EMBODIMENT AS AN ARCHIVE OF MEMORY: THE PHENOMENOLOGY OF TRAUMATIC EXPERIENCE IN CINEMA - Демура, А.А. (SWorldJournal, 2025)
This article examines embodiment as a means of registering and transmitting traumatic experience in audiovisual culture. Drawing on the phenomenological approaches of Maurice Merleau-Ponty and Dylan Trigg, as well as Vivian Sobchack’s theory of the embodi